2001
DOI: 10.1093/emboj/20.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Role of elementary Ca2+ puffs in generating repetitive Ca2+ oscillations

Abstract: Inositol (1,4,5)-trisphosphate (IP 3 ) liberates intracellular Ca 2+ both as localized`puffs' and as repetitive waves that encode information in a frequency-dependent manner. Using video-rate confocal imaging, together with photorelease of IP 3 in Xenopus oocytes, we investigated the roles of puffs in determining the periodicity of global Ca 2+ waves. Wave frequency is not delimited solely by cyclical recovery of the cell's ability to support wave propagation, but further involves sensitization of Ca 2+ -induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
257
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(286 citation statements)
references
References 45 publications
27
257
0
2
Order By: Relevance
“…In contrast to a constant Ca 2+ concentration, the nonlinear Fokker-Planck equation underestimates the results of the master equation. Nevertheless, the results in figure 7, which correspond to the stochastic fraction of the puff frequency, are in the same range as experimentally determined puff periods [8].…”
Section: Distribution Of First Passage Timesupporting
confidence: 77%
See 2 more Smart Citations
“…In contrast to a constant Ca 2+ concentration, the nonlinear Fokker-Planck equation underestimates the results of the master equation. Nevertheless, the results in figure 7, which correspond to the stochastic fraction of the puff frequency, are in the same range as experimentally determined puff periods [8].…”
Section: Distribution Of First Passage Timesupporting
confidence: 77%
“…A puff is the spontaneous opening of channels of a single cluster. Experimental and theoretical studies have suggested that puffs play a pivotal role in intracellular Ca 2+ dynamics [8,11]. These investigations put forward the idea that all global patterns like Ca 2+ waves foot on Ca 2+ puffs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar conclusions apply to spatially extended systems [12][13][14][15]. As concerns calcium dynamics, stochasticity has been mainly associated to external disturbances [10,11].…”
Section: Introductionsupporting
confidence: 58%
“…1) Dumollard and Sardet, 2001). This 'pacemaker Ca 2+ rise' is a hallmark of low-frequency (period >20 seconds) Ca 2+ oscillations generated under constantly elevated Ins(1,4,5)P3 levels (Jacob, 1990;Marchant and Parker, 2001), which further suggests that a single and sustained Ins(1,4,5)P3 increase regulates the ascidian MI pacemaker and the mouse MII pacemaker.…”
Section: The Organization Of the Er Network May Regulate The Ca 2+ Wamentioning
confidence: 90%